Etiological involvement of KCND1 variants in an X-linked neurodevelopmental disorder with variable expressivity - Kalm, Tassja; Schob, Claudia; Völler, Hanna; Gardeitchik, Thatjana; Gilissen, Christian; Pfundt, Rolph; Klöckner, Chiara; Platzer, Konrad; Klabunde-Cherwon, Annick; Ries, Markus; Syrbe, Steffen; Beccaria, Francesca; et al. (The American journal of human genetics, 2024)
Summary: Utilizing trio whole-exome sequencing and a gene matching approach, we identified a cohort of 18 male individuals from 17 families with hemizygous variants in KCND1, including two de novo missense variants, three maternally inherited protein-truncating variants, and 12 maternally inherited missense variants. Affected subjects present with a neurodevelopmental disorder characterized by diverse neurological abnormalities, mostly delays in different developmental domains, but also distinct neuropsychiatric signs and epilepsy. Heterozygous carrier mothers are clinically unaffected. KCND1 encodes the α-subunit of Kv4.1 voltage-gated potassium channels. All variant-associated amino acid substitutions affect either the cytoplasmic N- or C-terminus of the channel protein except for two occurring in transmembrane segments 1 and 4. Kv4.1 channels were functionally characterized in the absence and presence of auxiliary β subunits. Variant-specific alterations of biophysical channel properties were diverse and varied in magnitude. Genetic data analysis in combination with our functional assessment shows that Kv4.1 channel dysfunction is involved in the pathogenesis of an X-linked neurodevelopmental disorder frequently associated with a variable neuropsychiatric clinical phenotype.
Gesehen am 27.05.2024